Contribution of Distance Learning in Promoting Tertiary Women Education in Southern Punjab: Uzma Munawar* Muhammad Imran Rasheed** (PJDOL, 2023)
Pakistan is lacking in providing female education. This gap is fulfilled only by distance education. Allama Iqbal Open University has been providing education through distance and non-formal mode that covers all the areas including remote and for-flung areas where the existence of formal schools/colleges is impossible. The main purpose of this study was to evaluate the role of distance learning particularly among female. The objectives of this study were (a) to review the provision of women education, (b) to explain the contribution of distance learning in promoting female education, (c) to identify their problems and (d) to give suggestions for promotion of female education at tertiary level.